Mode hybridization in a gyrotron cavity with background plasma - Shcherbinin, V.I.; Zaginaylov, G.I. (Вопросы атомной науки и техники, 2014)
It is shown that a formation of hybrid modes (mode hybridization) in a gyrotron cavity occurs as their frequencies approach coincident points induced by background plasma. Such process, which is accompanied by a drastic change in fields and Q-values of the cavity modes, is studied with respect to some gyrotron parameters. Estimations are presented for several high-power continuous-wave (cw) gyrotrons.